2019
DOI: 10.1609/aaai.v33i01.33016610
|View full text |Cite
|
Sign up to set email alerts
|

Domain Agnostic Real-Valued Specificity Prediction

Abstract: Sentence specificity quantifies the level of detail in a sentence, characterizing the organization of information in discourse. While this information is useful for many downstream applications, specificity prediction systems predict very coarse labels (binary or ternary) and are trained on and tailored toward specific domains (e.g., news). The goal of this work is to generalize specificity prediction to domains where no labeled data is available and output more nuanced realvalued specificity ratings. We prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…Prediction of sentence specificity following the dictionary definition and pragmatically cast as "level of detail" was first proposed by Louis and Nenkova (2011), who related specificity to discourse relations. Sentence specificity predictors have since been developed (Louis and Nenkova, 2011;Li and Nenkova, 2015;Lugini and Litman, 2017;Ko et al, 2019). Insights from these featurerich systems and hand-code analysis (Li et al, 2016e) showed that sentence specificity encompasses multiple phenomena, including referring expressions, concreteness of concepts, gradable adjectives, subjectivity and syntactic structure.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Prediction of sentence specificity following the dictionary definition and pragmatically cast as "level of detail" was first proposed by Louis and Nenkova (2011), who related specificity to discourse relations. Sentence specificity predictors have since been developed (Louis and Nenkova, 2011;Li and Nenkova, 2015;Lugini and Litman, 2017;Ko et al, 2019). Insights from these featurerich systems and hand-code analysis (Li et al, 2016e) showed that sentence specificity encompasses multiple phenomena, including referring expressions, concreteness of concepts, gradable adjectives, subjectivity and syntactic structure.…”
Section: Related Workmentioning
confidence: 99%
“…Linguistically-informed specificity We use the system developed by Ko et al (2019), which estimates specificity as a real value. This system adopts a pragmatic notion of specificity-level of details in text-that is originally derived using sentence pairs connected via the INSTANTIATION discourse relation (Louis and Nenkova, 2011).…”
Section: Specificity Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…This has gained popularity in NLP (Zhang et al, 2017;Fu et al, 2017;Chen et al, 2018), however the difficulties of adversarial training are well-established (Salimans et al, 2016;Arjovsky and Bottou, 2017). Consistency regularization methods (e.g., self-ensembling) outperform adversarial methods on visual semi-supervised and domain adaptation tasks (Athiwaratkun et al, 2019), but have rarely been applied to textual data (Ko et al, 2019). Finally, Huang and Paul (2018) establish the feasibility of using domain adaptation to label documents from discrete time periods.…”
Section: Related Workmentioning
confidence: 99%